Development of An E-Module Flipbook Based on Problem Based Learning: Basic Concept of Local Government Accounting Materials - Anindya Putri Handini; Rochmawati Rochmawati (Actual Insight, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based E-Flipbook module for the subject of Basic Concepts of Local Government Accounting for Grade XI Accounting and Institutional Finance students at VHS State 1 Sooko Mojokerto and to evaluate its feasibility and effectiveness in supporting conceptual understanding. The study addresses the limited use of interactive digital teaching materials and students’ difficulties in understanding abstract and contextual accounting concepts in vocational education. This research employed the 4D development model (Define, Design, Develop, Disseminate), limited to the Develop stage, with a small-scale trial involving 20 students. Data were collected through expert validation by material experts, media experts, and learning practitioners, as well as student response questionnaires. The data were analyzed using descriptive quantitative techniques. The results showed that the developed module was highly feasible based on expert validation and received very positive responses from students. In addition, the integration of PBL into the digital flipbook format helped increase students’ learning motivation and supported deeper conceptual understanding of local government accounting material. Therefore, the module can be used as an innovative and student-centered learning medium in vocational accounting education.